MODAL SOSIAL PERAWAT PEREMPUAN MENGHADAPI PANDEMI COVID-19 DI RSUD DR. AGOESDJAM KETAPANG - Rupita, Rupita (Pusat Penelitian Pemberdayaan Perempuan, Gender, dan Anak UMRAH, 2022)
The coronavirus disease (COVID-19) situation in West Kalimantan ison a worrying threshold. Nurses, doctors and other health workers atthe forefront are among the affected components in this pandemicsituation. The purpose of this research is to map social models thatare strengthening for nurses. In addition to the body's immunity,social and family strengthening is able to be important as a capital orpsychic power. The method in this study is descriptive analysis, withdata collection through online interviews. Analysis of research datais carried out in conjunction with data collection, so the triangulationof data used is the triangulation of data sources. The study found thatfemale nurses were in hospitals. Dr. Agoesdjam had a strategy incarrying out tasks during pandemics. They strengthen each other.Here created a sense of mutual belonging between health workerswho are the vanguard of Covid-19 at dr. Agoesdjam KetapangHospital, with the creation of social capital that is intertwined suchas trust between colleagues, share values or share the feeling andexistence of social networking bonds